106 The impact of the new legislation on return to work in belgium. experiences of a large occupational health service. (24th April 2018) - Mylle, G; Verbeek, C; Bulterys, S; Godderis, L
Abstract : Introduction: In order to prevent long-term sickness, Belgian authorities reformed legislation on return to work (RTW). From 2017, employees have access to the occupational health physicians (OHP) to support their RTW. In addition, employers, general practitioners and medical advisors can refer to OHP for disability assessment. In this study, we investigated for which diseases and conditions, RTW was most successful. Methods: RTW trajectories carried out by IDEWE, one of the larges Occupational Health Services, were analysed. Differences according to gender, applicant, company size, duration and cause of absence were calculated and compared using Chi Square test. Results: 506 completed RTW trajectories were available for analysis: 33, 2% for male employees, 66, 8% for women. 59, 3% was initiated by the employee and 31, 6% by the employer. Most trajectories (29, 2%) were initiated in large companies, but 23, 9% was carried out in companies with less than 20 employees. Mental disorders (35, 5%) and musculoskeletal problems (33, 1%) represent 2/3 of the causes, which corresponds with the main causes of long-term sickness absence in Belgium. For 28, 3%, the occupational physician could realise return to work after making adjustments on the job. However, 60, 5% could no longer be re-employed at the same workplace (no possible job-person fit anymore). Re-integration appeared more successful for musculoskeletal disorders (37, 5%) than for mental problems (only 16, 6%). Finally, the chance on effective return to work reduced with duration of sickness absence. No significant differences in outcome were observed according to gender. Discussion: Re-integration was realised with the guidance of the OHP for almost 30% of the trajectories. RTW is most challenging for mental disorders: guidance to re-employment into a more suitable job is indispensable to avoid long-term absence. In order to achieve this, cooperation with medical advisers can be explored.